Photodynamic therapy for prostate cancer: Recent advances, challenges and opportunities - Xue, Qin; Zhang, Jingliang; Jiao, Jianhua; Qin, Weijun; Yang, Xiaojian (Frontiers in Oncology, 2022)
Over the past two decades, there has been a tendency toward early diagnosis of prostate cancer due to raised awareness among the general public and professionals, as well as the promotion of prostate-specific antigen (PSA) screening. As a result, patients with prostate cancer are detected at an earlier stage. Due to the risks of urine incontinence, erectile dysfunction, etc., surgery is not advised because the tumor is so small at this early stage. Doctors typically only advise active surveillance. However, it will bring negative psychological effects on patients, such as anxiety. And there is a higher chance of cancer progression. Focal therapy has received increasing attention as an alternative option between active monitoring and radical therapy. Due to its minimally invasive, oncological safety, low toxicity, minimal effects on functional outcomes and support by level 1 evidence from the only RCT within the focal therapy literature, photodynamic treatment (PDT) holds significant promise as the focal therapy of choice over other modalities for men with localized prostate cancer. However, there are still numerous obstacles that prevent further advancement. The review that follows provides an overview of the preclinical and clinical published research on PDT for prostate cancer from 1999 to the present. It focuses on clinical applications of PDT and innovative techniques and technologies that address current problems, especially the use of nanoparticle photosensitizers in PDT of prostate cancer.